Touraine–Solente–Gole syndrome: Clinical manifestation with bilateral true eyelid ptosis. (September 2019) - Akaranuchat, Nutthawut; Limsuvan, Papassorn
Abstract: Touraine–Solente–Gole syndrome (pachydermoperiostosis [PDP] or primary idiopathic hypertrophic osteoarthropathy [HOA]) is a rare hereditary disorder that is characterized by a triad of manifestations that consists of skin changes (pachydermia), abnormal bone and joint manifestations (periostosis and/or artritis), and digital clubbing (acropachia). Here, we report the case of 24-year-old male who presented with severe bilateral true eyelid ptosis. Physical examination revealed severe ptosis with poor function of the levator palpabrae superioris muscle, thickening of and deep grooves in facial skin (especially at the frontal region), and abnormal appearance of the scalp with accentuating folds and deep furrows (cutis verticis gyrata). Abnormal bone enlargement of the hands, knees, and feet was also observed. Frontal rhytidectomy and levator resection and advancement were performed to alleviate symptoms. At the short-term follow-up, the patient described being satisfied with the outcome of treatment. This patient will be routinely followed over the long term to evaluate disease progression. Although the cause of ptosis in most PDP is mechanical process or dysfunction, this case of PDP had bilateral true eyelid ptosis due to poor levator palpabrae superioris muscle excursion with coexisting signs and symptoms of complete form PDP. This finding highlights the need to investigate for bilateral true eyelid ptosis caused by abnormal levator palpabrae superioris muscle function in patients diagnosed with PDP.